ASUHAN KEBIDANAN PADA IBU NIFAS DENGAN PUTING SUSU LECET DI KLINIK ROHUL SEHAT DESA RAMBAH - Andriana,; Heny Sepduwiana, (Maternity and Neonatal : Jurnal Kebidanan, 2021)
The scope for achieving exclusive breastfeeding is still not satisfactory.The obstacles faced by breastfeeding mothers include blistered nipples. Some of the causes of sore nipples include improper breastfeeding technique, lack of milk production. The condition of blistered nipples causes pain that is felt by the mother and can also cause stress to the mother which makes it difficult for the mother to provide exclusive breastfeeding so that only a small amount of milk is obtained by the baby. The objective of the study is to carry out midwifery care for postpartum mothers day 2th Mrs.A (34 years old) with nipple blisters at the Rohul Sehat Clinic in Rambah village thoroughly with a midwife mindset approach 7 varney steps. The research was case study report with the 7 step of Varney method, that was done at Rohul Sehat Clinic in Rambah village. The subject of the study were postpartum mothers with nipple blisters Mrs. A P2A0 (34 years old) by breast care, oxytocin massage, teaching correct breastfeeding techniques. The study was done from December 19 to December 26 2020. The technique of data collection used interview and observation and secondary data used documentation and literature. After being conducted midwifery care to Mrs. A (34 years old) P2A0 with breast care, oxytocin massage, the correct breastfeeding technique for 2 days the problem has been resolved. It is expected to develop the further theory and practice of midwifery care of postpartum mothers with nipple blisters.